Kajian Literatur Trend dan Inovasi Pengembangan Book Creator Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Widowati, Ayu Saly; Agung Tri Prasetya; Bambang Subali; Ellianawati, Ellianawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The teaching of Civic education in primary schools plays a vital role in developing pupils’ critical, analytical and reflective thinking skills in line with the concept of deep learning. However, one of the problems frequently encountered is pupils’ difficulty in understanding the abstract concepts of religious diversity. This situation highlights the need for innovative learning media tailored to learners’ needs, one of which is the use of the Book Creator learning tool. This study aims to review various research findings regarding the development of Book Creator in Pancasila education during the period 2021–2025 using the Systematic Literature Review (SLR) method. The review process was conducted based on the PRISMA framework to ensure the transparency and accuracy of the research. Data were obtained from the Google Scholar and Scopus databases, with an initial total of around 1,000 articles, which were then screened to yield 25 articles meeting the inclusion criteria for further analysis. The analysis stage was carried out through bibliometric mapping using the Publish or Perish application, Microsoft Excel, and VOSviewer. Relevant articles were selected from national and international journals in accordance with the established criteria. The research findings indicate that the use of the Book Creator learning tool in Pancasila education in primary schools is effective in improving pupils’ learning outcomes through the use of three-dimensional visualisations. Furthermore, Book Creator also provides a more realistic, engaging, interactive and meaningful learning experience for pupils. Keywords: literature review, civic education, book creator